The Influence of Work Ethic and Commitment on the Social Competence of Teachers at Tembilahan Hulu Elementary School - Fadila, Rizka; Ayub Natuna, Daeng; Adi Putra, Jaya (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to determine the effect of work ethic and commitment on the social competence of teachers at SDN Tembilahan Hulu. This study used a quantitative approach with a survey method. The sample of the study was all 76 teachers taken by total sampling. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression analysis. The results showed that teachers' work ethic was in the high category, teachers' commitment was also high, and teachers' social competence was generally good. A partial test (t-test) showed that work ethic had a positive and significant effect on social competence, as did commitment, which also had a positive and significant effect. A simultaneous test (F-test) indicated that work ethic and commitment together had a significant effect on teachers' social competence. The Adjusted R Square value of 0.421 indicates that 42.1% of the variation in social competence can be explained by work ethic and commitment, while the rest is influenced by other factors outside this study. This study confirms that strengthening work ethic and commitment is an important strategy in improving teachers' social competence.